Hubungan Asupan Zat Gizi Makro dengan Status Gizi pada Anak Usia 2-5 Tahun di Puskesmas Karang Tengah Kabupaten Cianjur - Putri Rizkia; Nanan Sekarwana; Ratna Damailia (Bandung Conference Series: Medical Science, 2023)
Abstract. Nutritional status is an essential indicator of children's growth. Intake of macronutrients is one factor that can affect children's nutritional status. Lack of nutrient intake will affect children's nutritional status of children which can hinder growth and development of children. Problems that can arise from these conditions require knowledge of the factors associated with undernutrition and overnutrition, and one example is the factor of nutrient intake. This study aimed to determine the relationship between the intake of macronutrients and nutritional status in children aged 2-5 years at the Karang Tengah Health Center, Cianjur Regency. This study used a cross-sectional analytic observational method. The number of samples taken was 50 people with consecutive sampling. The research instrument was a 24-hour food recall questionnaire. The statistical test used was the Chi-Square with a significant level of ɑ = 0.05. The results showed that of the 50 samples, there were 5 children (10%) with less macronutrient intake, 32 children (64%) with sufficient macronutrient intake, and 13 children (26%) with more macronutrient intake. Most of the children have good nutritional status (70%). The results of the Chi-Square test showed that there was a relationship between the intake of macronutrients and obtained a value of p = 0.027. There is a significant relationship between the intake of macronutrients and nutritional status in children aged 2-5. Abstrak. Status gizi merupakan salah satu indikator yang penting bagi pertumbuhan anak. Asupan zat gizi makro merupakan salah satu faktor yang dapat mempengaruhi status gizi anak. Ketidakseimbangan asupan zat gizi akan mempengaruhi status gizi anak yang dapat menghambat tumbung kembang anak. Permasalahan yang dapat timbul dari kondisi tersebut memerlukan pengetahuan tentang faktor-faktor yang berhubungan dengan terjadinya gizi kurang dan gizi lebih, salah satu contohnya adalah faktor asupan zat gizi. Tujuan penelitian ini untuk mengetahui hubungan asupan zat gizi makro dengan status gizi pada anak usia 2-5 tahun di puskesmas karang tengah kabupaten cianjur. Penelitian ini menggunakan metode observasional analitik jenis cross-sectional. Jumlah sampel yang diambil sebanyak 50 orang dengan consecutive sampling Instrumen penelitian ini adalah kuesioner food recall 24 jam. Uji statistik yang digunakan adalah Chi-Square dengan tingkat signifikan ɑ = 0,05. Hasil penelitian menunjukkan dari 50 sampel terdapat 5 anak (10%) dengan asupan zat makro kurang, 32 anak (64%) dengan asupan zat makro cukup dan 13 anak (26%) dengan asupan zat makro lebih. Sebagian besar anak memiliki status gizi baik (70%). Hasil uji Chi-Square menunjukan ada hubungan antara asupan zat gizi makro diperoleh nilai p = 0,027. Ada hubungan yang bermakna antara asupan zat gizi makro dengan status gizi pada anak usia 2-5 tahun.